Third Gender Identity in Scientific and Practical Terms (The International Journal for Scientific Research, 2024)
The third gender is an individual who has different reproductive organs that are characteristic of females and males, meaning that someone who belongs to this gender may have female characteristics and at the same time male characteristics due to hormonal imbalance. Sex determination, sometimes known as sex determination, is determining the sex of the infant at birth. In most births, a relative, midwife, nurse, or doctor inspects the reproductive organs at birth, and the sex is determined conclusively without any doubt. Sex can also be distinguished and sex determined before Birth. In most cases, a child's sex corresponds to his or her gender identity, and the term “assignment” carries an implicit expectation that future gender identity will develop in line with physical anatomy, gender, and upbringing.In some Cases, a child gender does not match a future gender identity identification is a problem. People who have a different gender identity than their assigned gender may identify themselves as gender non-conforming (GNC). In the case of intersex individuals, gender characteristics are there may be complications if sex is made specific, it may not be consistent with child`s future gender identity, and sex determination through surgery and hormones may violate an individual`s rights.
Keywords: Third Gender; Homosexuality; Hormone & Genetic Disorder